PENERAPAN METODE FORCASTING DALAM MENENTUKAN JUMLAH SISWA BARU MENGGUNAKAN ALGORITMA SIMPLE LINEAR REGRESSION - Tajrin Tajrin; Mohammad Irfan Fahmi; Maikel Felix Ginting; Unika Nduru (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
New student admission is a school activity to recruit new prospective students that occurs regularly every year even in the middle of the teaching year. Madrasah Tsanawiyah (MTs) Al-Ittihadiyah is a school under the auspices of the Ministry of Religion. Where every year the school always accepts a fairly large number of new students around 300 people. This results in the school always having difficulties in preparing infrastructure facilities such as classrooms and teachers because the increase in the number of new students increases every year. This will happen repeatedly in schools from year to year. So that it will be an accumulation of data every year to help transform data into data information into useful information. This large amount of data opens up opportunities to generate useful information for schools. In this study, researchers see an opportunity to create a new technology that answers the needs and problems that have occurred so far. In determining the number of new students at MTs. Al-Ittihadiyah Pkl. Masyhur researchers used 2 dataset scenarios where scenario 2 datasets used a simple linear regression algorithm. In pre-processing data that produces prediction performance, namely Y = 71.9538 + 0.709269X, in the dataset for forecasting estimates for the number of new students if the registrant is 374 students, it will produce a prediction of new students of 337 students.